(untitled) (Journal of Ideas in Health, 2025)
Background: The cognitive dysfunction disorders are nowadays represented great health, social, and economic burden globally. Magnetic resonance imaging plays a major role in the evaluation of these disorders. This study aims to assess the relationship between the visual rating scale of global cerebral atrophy (GCA) & medial temporal lobe atrophy (MTA) scoring with age, white matter hyper-intensities, and cognitive value. Methods: A cross-sectional study carried out from 1st of November 2022 to 28th of February 2023 at the Magnetic Resonance Imaging unit of the Radiology department in Baghdad Teaching Hospital at Medical Complex in Baghdad city, Iraq. Sixty patients aged over 45 years with suspected cognitive abnormalities were included, while younger patients, those with territorial infarction, watershed infarction, or unwillingness to participate were excluded. Data were collected through a semi-structured questionnaire covering sociodemographic factors, chronic illnesses, cognitive status, MRI findings, and visual rating scales (Fazekas, Global Cortical Atrophy [GCA], and Medial Temporal Lobe Atrophy [MTA]). MRI was performed using a 1.5T Philips Achieva Nova scanner, and cognitive assessment was conducted with the Mini-Mental State Examination (MMSE). Results: The mean age of participants was 62.4 ± 8.8 years, with males slightly predominating (55%). Chronic diseases were common, particularly hypertension (57.2%). Cognitive assessment revealed 51.7% with normal cognition, 18.3% with mild cognitive impairment, and 30% with dementia. Higher Fazekas, GCA, and MTA scores were significantly associated with dementia (p<0.05). MTA scores were significantly elevated in Alzheimer’s disease (p<0.001), while vascular etiologies were strongly associated with higher GCA, Fazekas, and MTA scores (p<0.05). Non-strategic lacunar ischemia showed higher Fazekas scores compared to strategic types (p=0.006). Increasing age was significantly linked to dementia, vascular pathology, and higher atrophy scores. Conclusion: These findings suggest a strong correlation between structural brain changes observed on MRI and cognitive decline, highlighting the importance of visual rating scales in clinical assessment.